The unpredictable nature of microbiological responses to metals in real-world contaminated soils: A review - Schoffer, J. Tomás; Stuckey, Jason W.; Yáñez, Carolina; Ginocchio, Rosanna; Neaman, Alexander (Frontiers in Environmental Science, 2025)
Microbial responses, such as biomass or enzymatic activity, are commonly used to evaluate metal toxicity in contaminated soils. However, multiple studies have demonstrated the existence of microbial tolerance and resilience to metals. The adaptive responses of soil microorganisms to metal stress may compromise their suitability for evaluating metal toxicity in contaminated soils. Further evaluation is needed to establish the robustness of microbiological responses as metal toxicity indicators in contaminated soils. In this review, we focus on real-world contaminated soils, excluding artificially contaminated soils. We reviewed studies that reported the values of effective concentrations at 10% and 50% (EC10 and EC50) of soil metals (either total, extractable, or soluble concentrations) for soil microbiological response in real-world contaminated soils. However, there are also studies demonstrating that the effects of soil metals on microbiological responses range from toxic (negative) in soils with metal concentrations below the mean reported EC10 values to stimulatory (positive) in soils with metal concentrations above the mean reported EC50 values. Hence, in some cases, microorganisms’ responses indicate metal toxicity at low soil metal concentrations, at which toxicity is not expected. In contrast, in other cases, microorganisms are stimulated by metals at high soil metal concentrations, at which stimulatory responses are not expected. Further, soil microbiological responses can be influenced by soil physicochemical properties rather than soil metals concentrations even at metal concentrations above the mean reported EC50 values, at which metal toxicity for soil microorganisms is expected. In summary, the unpredictable nature of microbiological responses to metals makes them unreliable indicators of metal toxicity in real-world contaminated soils.